Strategies of Learning Through The Donkey bridge and Singing in Early Children at Tpq Al-Ikhlas Lebakbarang - Rifani Raniasati; Inayah Priyatun (Social Sciences and Education Research Review)
Understanding is the result of learning from what has been read or heard, and can provide other examples that have been explained by the teacher. In the learning process, every child has different abilities. So sometimes, there are children who are left behind (understanding) from their classmates. Sometimes children feel pressured (stressed) because they are left behind from their friends. There are many cases where children don't want to study anymore because they don't go to class. Because when he doesn't go to the next class, he will most likely feel different from his friends both in terms of greater physicality and from a less intelligent level (feeling stupid). This study uses a descriptive approach, where the research aims to describe a phenomenon. Based on this theory, the researcher intends to use this approach because it can make it easier for researchers to describe the application of Learning Strategies